PHENOLIC COMPOUNDS CONTENT, ANTIOXIDANT, ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF RED ONIONS SKIN - ALBANDARY N. A., (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to search and identify potentially active antibacterial, anti-oxidants, and antifungal compounds in red onion skin. Phenolic-rich onion extract was obtained from red onion skin extracted with methanol 70% for 2 h. The extract's antioxidant, antibacterial and antifungal activities were determined. The extract demonstrated the maximum DPPH radical scavenging activity (96% ±3.8) at 2000 g / mL, according to the findings of this study. Anthocyanin concentration, total soluble solids (TSS), total phenolics (TPCs), and, total flavonoids (TFs) in tested sample can all be linked to antioxidant ability. For all microorganisms tested, the minimum inhibitory concentration (MIC) of the tested sample was 200 g/mL. A red onion skin methanolic extract obtained ultimate suppression at 1000 g/mL after 7 days of incubation at 25 °C, equating to a 77% linear growth reduction of Fusarium graminearum. As a result, the outer skin of the red onion could be employed in nutritional fortification or nutraceutical preparations to improve health outcomes.